Godność ciała ludzkiego według Tertuliana. Analiza komentarzy do tekstów Rdz 1, 26-27; 2, 8; 1Kor 3, 16 - Turek, Waldemar (Vox Patrum, 2015)
The present paper discusses the dignity of human body as treated in selected texts from Tertullian’s De resurrectione mortuorum and Adversus Marcionem. Because Tertullian argues primarily on the basis of Sacred Scripture, special consideration will be given to his exegesis of Genesis 1: 26-27 and 2: 8. Tertullian demonstrates that the creation of the human body is the direct work of God who creates it, precisely with the future Incarnation of his beloved Son already in mind. Tertullian describes, against Marcion, the dignity of the human body as ensuing from the gift of freedom which man received from God at the act of creation. The human body is the instrument through which man receives spiritual gifts. We therefore can call it the „foundation of salvation”. In his polemic against the followers of Plato and the gnostics, Tertullian demonstrates that the human body and the entire „man” is called to be a temple of God (cf. 1Cor 3: 16).